Câncer de colo uterino no Sistema Único de Saúde em Sergipe : avaliação dos custos e características sociodemográficas das internações hospitalares no período de 2008 a 2015 - Silva, Ana Maria Fantini (2017)
Cervical cancer is one of the leading causes of cancer death in the world. In Brazil, it is the 3rd cause of neoplasia in women. The situation in Sergipe is even worse, been responsible for the 2nd cause of death by malignant tumors in women. Since 1997 the cervical cancer prevention program, through the application of Papanicolaou test, is one of the priorities in the primary care policies in Brazil. Logistic and technical difficulties, especially in remote areas, impose important limitations for the universalization of the program. These difficulties are more clearly observed in North and Northeast regions, maintaining cervical cancer occurrence and mortality rates above national average even after 15 years of the beginning of the screening program. Studies evaluating the evolution of the cervical cancer prevention program through epidemiological markers are rare in Brazil and Sergipe. There is a worldwide tendency of using indicators from hospital activities for avoidable conditions as a way of evaluating the effectivity of primary care. The current study evaluated cervical cancer hospitalizations in Sergipe, in the time period between 2008 and 2015, from data available in DATASUS. Costs, sociodemographic characteristics and temporal modifications after the introduction of Papanicolaou test as a priority in primary care are evaluated. In the period of the study there were 873 hospitalizations. The median age was 46 years and the patients were hospitalized for a medium period of six days. The median hospitalization cost was R$1,766.00 and the cost for surgical hospitalization was three times greater than the one clinical hospitalizations. After the population adjust, there was a predominance of patients from cities other than the capital of Sergipe. In the temporal analysis there was a reduction of hospitalizations by approximately 10% per year, both for the population living in the capital and the population living in the other cities of the state. There was a statistically significant reduction in the number of clinical hospitalizations and a tendency to reduction for surgical hospitalizations. Therefore, it can be concluded that there was a significant decrease in the number of cervical cancer hospitalizations, and this decrease can be correlated to improvements in health care and the consolidation of the screening program in the study period.